2017
DOI: 10.18295/squmj.2016.17.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes Towards Basic Life Support Among Health Students at a Saudi Women’s University

Abstract: Objectives: Awareness of basic life support (BLS) is paramount to ensure the provision of essential life-saving medical care in emergency situations. This study aimed to measure knowledge of BLS and attitudes towards BLS training among female health students at a women's university in Saudi Arabia. Methods: This prospective cross-sectional study took place between January and April 2016 at five health colleges of the Princess Nourah bint Abdulrahman University, Riyadh, Saudi Arabia. All 2,955 students attendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
1
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 22 publications
2
36
1
7
Order By: Relevance
“…These findings are in agreement with those of previous research from Saudi Arabia, which have consistently shown poor BLS awareness but favorable attitudes towards BLS training according to Al-Mohaissen 15 , Al-Turki et al 4 , Alanazi 1 . The knowledge score observed in the present study is based on the critical question which can be verified by the previous research Al-Mohaissen et al Also, the knowledge scores observed in the current study were similar to those reported among medical students in Princess Nourah bint Abdulrahman University, Riyadh, Saudi Arabia in Al-Mohaissen study 15 ; the question students were unable to answer shows that the students lack understanding of some basic concepts regarding the practice.…”
Section: Discussion:-supporting
confidence: 90%
“…These findings are in agreement with those of previous research from Saudi Arabia, which have consistently shown poor BLS awareness but favorable attitudes towards BLS training according to Al-Mohaissen 15 , Al-Turki et al 4 , Alanazi 1 . The knowledge score observed in the present study is based on the critical question which can be verified by the previous research Al-Mohaissen et al Also, the knowledge scores observed in the current study were similar to those reported among medical students in Princess Nourah bint Abdulrahman University, Riyadh, Saudi Arabia in Al-Mohaissen study 15 ; the question students were unable to answer shows that the students lack understanding of some basic concepts regarding the practice.…”
Section: Discussion:-supporting
confidence: 90%
“…1 Adequate awareness of basic life support (BLS) and cardiopulmonary resuscitation (CPR) is an important global issue to ensure that individuals can provide necessary life-saving care in emergency situations. 2 It is an integral part of emergency resuscitative care that aims to retain sufficient ventilation and Poudel M et al…”
Section: Introductionmentioning
confidence: 99%
“…A previous survey from Saudi Arabia demonstrated a low level of interest in and knowledge of CPR among university students. 20 Improving health education and conducting awareness campaigns regarding the benefits and methods of performing CPR are recommended to address this issue in the Omani community. Furthermore, ensuring the availability of automated electrical defibrillators in public places should be encouraged as these may be of benefit in certain situations.…”
Section: Discussionmentioning
confidence: 99%